The Impact of Divorce on Children's Psychological Development - Nurul Ilma B; Intan Mawardah (Socrates: Journal of Education, Philosophy and Psychology, 2025)
Marriage is a sacred bond that unites two individuals in love, and in Islamic teachings is seen as a lifelong commitment. However, separation in a household is often a difficult reality to accept, impacting not only the couple but also their children. For families, divorce is a difficult test that can affect harmony. When children are in the midst of parental conflict that leads to separation, the impact on their development becomes a matter of concern. Divorce is a situation in which a married couple decides to live separately for various reasons. This study aims to identify the psychological impact experienced by children due to parental divorce. This study was conducted through a literature review analyzing 10 scientific journals discussing the effects of divorce on child psychology. The results show that divorce can trigger psychological disorders such as anxiety, feelings of insecurity, and depression in children. Furthermore, the impact on cognitive aspects is evident in decreased concentration in learning and others.